Foreign bank lending and information asymmetries in China - Pierre Pessarossi; Christophe J. Godlewski; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
This paper considers whether information asymmetries affect the willingness of foreign banks to participate in syndicated loans to corporate borrowers in China. In line with theoretical literature, ownership concentration of the borrowing firm is assumed to influence information asymmetries in the relationship between the borrower and the lender. We analyze how ownership concentration influences the participation of foreign banks in a loan syndicate using a sample of syndicated loans granted to Chinese borrowers in the period 2004-2009 for which we have information on ownership concentration. We observe that greater ownership concentration of the borrowing firm does not positively influence participation of foreign banks in the loan syndicate. Additional estimations using alternative specifications provide similar results. As foreign banks do not react positively to ownership concentration, we conclude that information asymmetries are not exacerbated for foreign banks relative to local banks in China. Moreover, it appears that increased financial leverage discourages foreign bank participation, suggesting that domestic banks are less cautious in their risk management.
URN:NBN:fi:bof-201408072058
Keywords: 330